Nanostructure to microstructure self-assembly of aliphatic polyurethanes: The effect on mechanical properties - Mishra A.; Aswal V.K.; Maiti P. (My University, 2025)
We report the step by step self-assembly from nanostructure to microstructure (bottom-up approach through X-ray diffraction (1.6 nm), small angle neutron scattering (SANS) (11.6 nm), atomic force microscopy (70 nm smaller crystallite from enlarged image and 450 nm greater crystallites), and polarizing optical microscope (2 μm)) of aliphatic polyurethanes (PU) in contrast to aromatic polyurethanes depending on hard segment content (HSC). Polyurethanes of 10 to 80% HSC have been synthesized by using appropriate amount of polyol and chain extender. The effect of self-assembled patterns on mechanical properties both in solid and liquid state has been established exhibiting structure-property relationship of supramolecular polyurethanes. The crystallinity enhances but the degradation temperature decreases with increasing HSC. The characteristic length (measure of gap between lamellar crystallites), as revealed from SANS, gradually decreases with increasing HSC suggesting compactness of the crystallites through extensive hydrogen bonding. The Youngs modulus increases with increasing HSC with a percolation threshold of hard segment (50%) while the toughness improves up to 30% HSC followed by gradual decrease in presence of bigger crystallites which promote brittle fracture. The origin of self-assembly in aliphatic PUs has been demonstrated through electronic structure calculations to form a loop structure with minimum intermolecular distance (2.2 Å) while that distance is quite large in aromatic polyurethanes (4.6 Å) that cannot form hydrogen bonds. The unique splintering of domain structure and its subsequent reformation under dynamic shear experiment has been established. © 2010 American Chemical Society.